Gendered Perspectives and Performativity in Sayaka Murata’s Convenience Store Woman: An Evaluation on Keiko’s Cognitive Responses and Societal Challenges - A. Mercy Sanjana; A. Aashrita Mariam (ILN Journal: Indian Literary Narratives, 2024)
This study examines Sayaka Murata’s novel, Convenience Store Woman from a gendered perspective. It delves into Keiko’s cognitive responses to social interactions, utilising research to demonstrate how her unique worldview offers a corrective approach to life. Drawing upon Judith Butler’s theory of Gender Performativity, the article argues that Keiko rejects societal gender norms. This analysis explores Keiko's cognitive processes and performative behaviours that challenge the gender constructs and expectations which are imposed by society. The study also explores the convenience store setting as a sanctuary for Keiko, a realm that serves as a distinct separation from the external world.